2014
DOI: 10.1080/17470218.2013.870589
|View full text |Cite
|
Sign up to set email alerts
|

Do Part–Whole Relations Produce Facilitation in the Picture–Word Interference Task?

Abstract: Three experiments used the picture-word interference task to evaluate competing models of lexical access in spoken word production. Both the presence of a part-whole relation and association between the target and the interfering word were manipulated. Part terms associated with targets produced facilitation at early stimulus onset asynchronies (SOAs; -300 ms in Experiment 1, -300 and -150 ms in Experiment 3), but not at SOA 0 ms. Otherwise, part terms tended to produce interference, with unassociated part ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 27 publications
8
37
2
Order By: Relevance
“…Thus, whereas the responseexclusion hypothesis meets with theoretical and empirical difficulty (e.g., Aristei and Abdel Rahman, 2013;Abdel Rahman and Aristei, 2010;Abdel Rahman and Melinger, 2009;Hantsch and Mädebach, 2013;La Heij, Kuipers, and Starreveld, 2006;Mädebach, Oppermann, Hantsch, Curda, and Jescheniak, 2011;Coltheart, 2012, 2014;Piai et al, 2011Roelofs et al, 2011Sailor and Brooks, 2014;Starreveld, La Heij, and Verdonschot, 2013), the competition hypothesis remains a viable account of word selection in word production. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, whereas the responseexclusion hypothesis meets with theoretical and empirical difficulty (e.g., Aristei and Abdel Rahman, 2013;Abdel Rahman and Aristei, 2010;Abdel Rahman and Melinger, 2009;Hantsch and Mädebach, 2013;La Heij, Kuipers, and Starreveld, 2006;Mädebach, Oppermann, Hantsch, Curda, and Jescheniak, 2011;Coltheart, 2012, 2014;Piai et al, 2011Roelofs et al, 2011Sailor and Brooks, 2014;Starreveld, La Heij, and Verdonschot, 2013), the competition hypothesis remains a viable account of word selection in word production. …”
Section: Discussionmentioning
confidence: 99%
“…Muehlhaus et al (2013) selected part-whole stimuli that were strong associates using cue-target free association norms. Consistent with this explanation, Sailor and Brooks (2014) found that part-distractors produced facilitation only when they were associated with the target. When not associated with the target, part-distractors produced an interference effect compared to parts unrelated to the target object (Experiments 1 & 3).…”
Section: Bumper)mentioning
confidence: 61%
“…This manipulation allows for an investigation of the role of feature distinctiveness with respect to reports of semantic facilitation with object-part relations in PWI (Costa, et al, 2005;Muehlhaus et al, 2013;Sailor & Brooks, 2014) Finally, Chapter 5 summarises the evidence from Chapters 2, 3 and 4, with respect to the alternative accounts of speech production that have been proposed based on the empirical challenges to the lexical selection by competition account (Mahon, et al, 2007;). …”
Section: Outline Of the Dissertationmentioning
confidence: 99%
See 2 more Smart Citations